2021
DOI: 10.1088/1361-6528/ac0eaa
|View full text |Cite
|
Sign up to set email alerts
|

A self-powered photoelectrochemical ultraviolet photodetector based on Ti3C2T x /TiO2 in situ formed heterojunctions

Abstract: Transition metal carbides and nitrides (MXenes), as a large family of emerging two-dimensional materials, have demonstrated extraordinary performance in many fields such as electronics, optics and energy storage. However, their susceptibility to oxidation during preparation and storage in ambient air environment is undesirable for long-term and stable applications. Here, we have demonstrated that the spontaneous oxidation of Ti3C2T x can be harnessed ingeniously to prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Both pulse widths, that are in the range of 8-154 ps, and fall times (400-800 ps range), are orders of magnitude shorter than in similar devices that were previously reported. [19,[34][35][36][37][38][39][40][41][42][43][44][45]47] Figure 3d shows the impulse response of the device under +10 V bias, as the illumination power is swept from 16 to 88 µW. A double exponential model consisting of a fast and a slow component fits this data well (Table S3., Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both pulse widths, that are in the range of 8-154 ps, and fall times (400-800 ps range), are orders of magnitude shorter than in similar devices that were previously reported. [19,[34][35][36][37][38][39][40][41][42][43][44][45]47] Figure 3d shows the impulse response of the device under +10 V bias, as the illumination power is swept from 16 to 88 µW. A double exponential model consisting of a fast and a slow component fits this data well (Table S3., Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[69][70][71][72] The presented data shows that this BE/MX-S-MX device is orders of magnitude faster than other 2D devices. Figure 6 compares the responsivity and time response of previously reported MXene based devices that include TiO 2 , [34,35] CsPbBr 3 , [36,37] GaN, [38,39] Bi (with Nb 2 C), [40] MoS 2 , [41] n-Si, [43] InSe, [44] GaAs, [26,47] ZnO, [46] and Ge, [45] as well as other devices such as MoS 2based, [42] Graphene, [19] and Graphene/Si [73] ones. The response of our BE/MX-S-MX device shows excellent responsivity, and time response by simultaneously optimizing the 2D contact with semiconductor structure (Figure 6).…”
Section: Light Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A few works have reported the combination of TiO 2 with MXenes in UV PDs. Wang et al [31] utilized the spontaneous oxidation of Ti 3 C 2 T x to prepare Ti 3 C 2 T x /TiO 2 in situ forming 2D-3D heterojunctions, which exhibited a responsivity of 2.06 mA W −1 at 0 V (360 nm, 48.5 µW cm −2 ). The rise/decay time was 45 and 69 ms. Yang et al [32] demonstrated a controllable in situ-oxidation strategy for large-scale 3D-networked Ti 3 C 2 T x -TiO 2 heterostructure for PDs, the responsivity of which achieved 0.06 mA W −1 at 5 V (405 nm, 8.58 mW cm −2 ).…”
Section: Introductionmentioning
confidence: 99%
“…SEM results also confirm the formation of titanium oxide (TiO 2 ) nanoparticles on un-delaminated MXenes which are stored at ambient environments [142]. Fortunately, a new strategy by controlling the oxidation process of MXenes has been investigated by several groups, which overturns the aforementioned oxidation disadvantage and further improves the device performances [124,134,143]. In 2018, Chertopalov et al demonstrated that partially oxidized Ti 3 C 2 MXene thin films exhibit obvious photoresponse in the UV region (Fig.…”
Section: Research: Reviewmentioning
confidence: 87%